Detection of Nutrients and chemicals in food products using sensors in smart phones (International Journal of Engineering and Computer Science, 2017)
Sensors are the physical devices whose function is to sense/detect the changes around its environment, and provides a corresponding output. There are differenct types of sendors available which are used for discrete applications. A Biosensor is a device used to detect nutrients (protein, vitamin etc) or chemicals (antioxidants, carbon contents etc). This paper presents the idea of making a costeffective device using sensors to detect nutrient, chemical contents in foods like vegetables fruits etc and the output of these must be displayed in smart phones.